2015
DOI: 10.1099/jgv.0.000295
|View full text |Cite
|
Sign up to set email alerts
|

Tracking vaginal, anal and oral infection in a mouse papillomavirus infection model

Abstract: Noninvasive and practical techniques to longitudinally track viral infection are sought after in clinical practice. We report a proof-of-principle study to monitor the viral DNA copy number using a newly established mouse papillomavirus (MmuPV1) mucosal infection model. We hypothesized that viral presence could be identified and quantified by collecting lavage samples from cervicovaginal, anal and oral sites. Nude mice infected at these sites with infectious MmuPV1 were tracked for up to 23 weeks starting at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(125 citation statements)
references
References 66 publications
6
119
0
Order By: Relevance
“…While we studied skin disease here, MmuPV1 also replicates at oral, anal, and vaginal sites, suggesting how this model might be further improved (80). Using mice with persistent benign MmuPV1 papillomas, we demonstrate immune-directed clearance through vaccination with a naked DNA, hCRT-mE6mE7mL2, administered with electroporation.…”
Section: Discussionmentioning
confidence: 99%
“…While we studied skin disease here, MmuPV1 also replicates at oral, anal, and vaginal sites, suggesting how this model might be further improved (80). Using mice with persistent benign MmuPV1 papillomas, we demonstrate immune-directed clearance through vaccination with a naked DNA, hCRT-mE6mE7mL2, administered with electroporation.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptrol (Ortho Options, over the counter) as previously described . Tongues 519 were withdrawn using a sterile forceps and microneedles were used to wound the ventral surface 520 of the tongues (Cladel et al, 2016;Hu et al, 2015). Twenty-four hours after wounding, eight 521 female and six male Hsd: Nu athymic mice were again anesthetized and challenged with 522 infectious MmuPV1 virions (1×10 8 viral DNA equivalents) via the tail vein.…”
Section: Analyses 512mentioning
confidence: 99%
“…The virus can infect both cutaneous and mucosal epithelium (Cladel, Budgeon et al, 2013a; Cladel, Budgeon et al, 2015a;Hu, Budgeon et al, 2015)…”
Section: Preclinical Models (In Vivo)mentioning
confidence: 99%
“…Experiments have shown that back, muzzle and tail skin are susceptible sites and led the initial investigators to conclude that this virus shows a cutaneous tropism (Ingle, Ghim et al, 2011). However, additional studies demonstrated that secondary infections could be found in mucosal tissues of the vaginal, anal and oral cavities (Cladel, Budgeon et al, 2013a;Cladel, Budgeon et al, 2015b) and that infections could be experimentally induced at these sites with ease (Cladel, Budgeon et al, 2015a; Hu, Budgeon et al, 2015). More recent studies in our lab with several strains of mice with varying levels of immune deficiency have indicated that there are unknown mechanisms of altered tissue tropism in which vaginal sites in two strains show active and persistent infections whereas direct infection of tail skin showed no signs of clinical disease.…”
Section: Preclinical Models (In Vivo)mentioning
confidence: 99%